Feasibility Analysis of Limestone Industry Development as a Leading Mining Product of Rembang Central Java District - Lukman; Sujianto, Agus Eko; Sutarno; Nas, Chairul (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study was to determine the economic feasibility and to determine the strength and opportunities for the development of the limestone processing industry as a superior product in Rembang Regency based on analysis NPV, IRR, ROI, Payback Period, Benefit Cost Ratio and BEP. The results of this study state that the brick mining industry is economically viable and has good strength and opportunities to be developed. SWOT Analysis of internal strength & weakness (IFAS), external opportunity & threat (EFAS) and Factors Analysis Summary (SFAS) strategy factors in the limestone industry that the position of the limestone industry shows that the limestone industry has good strength and opportunity to develop as a product leading.